Теоретичні основи управління активами та пасивами підприємства - Насібова, Ольга Вікторівна; Дзюба, Вікторія Миколаївна (Аудиторська фірма "Аналітик", 2018)
Досліджено теоретичні питання ефективності управління активами та пасивами підприємства. Розглянуто поняття пасиву і активу підприємства, як управлінських категорій. Систематизовано класифікаційні ознаки активів підприємства. Визначено переваги і недоліки власного та позичкового капіталу при формуванні його структури на підприємстві.

The asset and liability management is important for effective work of any entity. An enterprise, which aims to create conditions for sustainable development and increase profitability, should use not only steady rules of economic theory when making managerial decisions, but also be guided by time trends in market relations. Asset management of an enterprise is a complex process, which consists in the correct formation and use of assets by volume, composition, structure with taking into account the influence on them of numerous factors of the internal and external environment. Management of the formation of assets is the primary stage in the development of any enterprise and is carried out at the different stages of the life cycle from the establishment of the enterprise, modernization, expansion and reconstruction to the construction of the new structural objects of the operating enterprise. Formation of assets requires the definition of necessary amount of start-up capital, asset turnover rate and level of their liquidity, profitability. The main goal of the formation of management assets is the creation of conditions that would help accelerate the turnover of assets that will reduce the time of the turnover of resources, increase profitability work of the enterprise and increase its profits. Asset management is carried out directly during the manufacturing process. One of the main tasks of such a management is the implementation of measures that will facilitate the optimization of the composition of assets. Optimization the assets are aimed at ensuring their full use, and by choosing the option of such use, which will bring the most benefit for the company. The main objective of liabilities management of the company is to ensure stable financing activities of enterprise. For effective asset and liability management an enterprise needs: an adequate information base that must be sufficient and reliable for a thorough analysis for the purpose of managerial influence; providing uniform methodological principles to the organization and keeping records of certain components of assets, liabilities and capital, which determines comparing data base of information; the effectiveness of management solutions ensures the transparency of information base, which becomes of particular importance during the economic periods of crisis, corruption and instability of the economy.
Theoretical bases of the management of the assets and passives of the enterprise
Keywords: активи; управління активами; пасиви; управління пасивами; підприємства; assets; asset management; liabilities; liability management; enterprise